Policy and Food Consumption: What Nutrition Guidelines Are Swiss Children Meeting and What Determines Adherence? - Rangelov, Natalie; Nogueira Avelar e Silva, Raquel; Suggs, L. Suzanne (Frontiers in Nutrition, 2021)
Objectives To describe children’s adherence to the Swiss Society for Nutrition dietary (SSN) guidelines, assess determinants of adherence, and compare these findings with a previous study in the same population. Methods Data from 312 children ages 5-12 were collected through a survey and a 2-day food record. The associations of children and parent-related factors with children’s adherence to guidelines were assessed by logistic regression analyses. Results SSN guidelines were not met for any food category, although there were improvements: vegetables (4.5% in this study vs. 0% in previous study), sweets, snacks, & soft drinks (12.5% vs. 9.5%), and fruit (45.5% vs. 10.4%). Higher children’s BMI was associated with higher adherence to guidelines for protein intake. Higher parental BMI was associated with higher adherence for vegetables. Parental lower educational level was associated with higher adherence for cereal. Conclusion Despite improvements since the last eating behavior assessment in this population, children consume too little fruit, vegetables, cereal, and milk & dairy products, and too much SSD and proteins. Further efforts are needed to promote healthy eating to children and achieve adherence to guidelines. Key Words Children, Eating Behavior, Dietary Guidelines, Guideline Adherence, Determinants